Business Model Canvas ENT 300 : Surprise Delivery by A&I Production / Nurul Izzati Ahmad Shabri - Ahmad Shabri, Nurul Izzati (2020)
Surprise Delivery by A&I Production is a service that provides surprise delivery and surprise events for special events such as Birthday Celebration, Anniversary, Special Day and Proposal. It is a well-known surprise service in Kedah especially in the Alor Setar and Sungai Petani areas. Surprise Delivery by A&I Production was founded by Miss Nurul Izzati and her friend, Mr Adlan Shahmy Azizan, a graduate student who began this service while they were still studying in UiTM Kedah. In the first beginning, their target market was students in UiTM Kedah only, but now they expand their market after encouraging response by their served customers. At this moment, Surprise Delivery by A&I Production has served more than 250 customers after 8 months operating with a small budget but gaining huge returns. Surprise Delivery by A&I Production is planning to expand their markets into Penang Island and Perlis in the next few weeks after getting high requests from customers in both areas.